The Importance and Roles of Linguistics?In Islamic Studies (Integration of Linguistics With Religious Studies) - Saifuddin Ahmad Husin (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
Knowledge integration has been studied as the process of incorporating new informa- tion into a body of existing knowledge with an interdisciplinary approach. Language is not only the object of scientific study of linguistics, but also the object of study of other related disciplines. The importance of language in many studies and disciplines of knowl- edge has led to its status as a condition sin qua non to true understanding of other scientific objects of disciplines of knowledge. The mastery of Arabic language for ex- ample is a must for the study of Islamic religious texts. The religion of Islam places language on a very high position that it is explicitly mentioned in the Quran as one of the signs of the existence of God.